SUBSTITUSI JAMUR MERANG (Volvariella volvaceae) DAN TEPUNG KORO PEDANG TERMODIFIKASI (Canavalia ensiformis L.) PADA PEMBUATAN BAKSO SAPI - Ahmad Nafi'; Wiwik Siti Windrati; Nurud Diniyah; Mega Pusva Sintha (Faculty of Agricultural Technology, University of Jember, 2014)
Modified jack bean flour consists high protein which has a potential function for meatball product. This research was intended to identify the effect of the use of mushroom and modified jack bean as substituting ingredients of beef physical and chemical of the produced meatballs. The research used randomized block design (RBD), which consisted of one factor with 3 replications in each treatment, that is, the ratio variation of mushroom : modified jack bean flour : beef (F), in ratio of F1 (30%:10%:60%) , F2 (40%:15%:45%), F3 (50%:20%:30%), F4 (60%:25%:15%), F5 (70%:30%:0%) and 100 % beef. The data obtained were processed using analysis of variance. If there were significantly different data then, further test would be conducted using DMRT (Duncan Multiple Range Test) at 5% level. The effectiveness test results showed that the best value was from formulation F1 (ratio of mushroom : jack bean : beef at 30 : 10 : 60). Meatballs produced from the treatment had color brightness value of 54.58, texture 435.20 g/5mm, water content 53.88%, ash content 1.83%, fat content 1.37%, protein content 9.42%, carbohydrate content 33.50%, and fiber content 2.72 %.Keywords: Volvariella volvaceae, jack bean flour, meatball, protein, fat